Geo-Spatial Evolution of Desertification in Cholistan Desert of South Punjab, Pakistan - Muhammad Zulqadar Faheem; Muhammad Farrukh Shahzad; Muhammad Waseem Iqbal; Muhammad Asif (Indus Journal of Social Sciences, 2025)
Satellite remote sensing has become a dependable geospatial technology for accurately evaluating land use and land cover across global, regional or local scales. This research aims to assess changes in land cover and land use in the Cholistan Desert through Supervise classification and NDVI, NDbaI and TGSI indices, which is located in southern Punjab, Pakistan. Landsat data has been a reliable source for historical images of the Earth’s surface over the past 25 years due to its consistency and practicality. The present research utilizes satellite data from Landsat 5 TM for the years 1996, 2002, and 2008, along with Landsat 8 OLI for the years 2014 and 2020. To calculate the area percentage, change and annual dynamic rate of change at discrete time intervals, maximum likelihood supervised classification and change detection algorithms are necessary. In this work, the methods employed for change detection utilize remote sensing indices like the normalized difference vegetation index, the top grain soil index, and the normalized difference bareness index. Between 1996 and 2020, the findings show that agricultural land grew at a rate of 2.3%, while uncultivated land diminished at a dynamic rate of 0.5%. The linear regression analysis reveals a significant R2 of 0.99 for the relationship between the population growth rate and agricultural growth rate at the 0.03 significance level, as well as a significant R2 of 0.58 for the relationship between agricultural growth rate and barren land reduction rate. A comparison of the district’s vegetation and bareness indices reveals a 16.8% increase in vegetation and a 13.4% decrease in bareness, with the latter change mainly occurring in the south of the district, towards lesser Cholistan Correlation coefficients between vegetation and the bareness index were 0.83 in 1996 and 0.91 in 2020. As a consequence of considerable alterations in land use, the natural environment and arid ecosystem of the study area are deteriorating. This study can act as a template for local stakeholders aiming to enhance land use planning in the district by identifying areas that are most vulnerable to changes in land use.